Venous sinus stenting for the treatment of isolated pulsatile tinnitus: Results of a prospective trial. Issue 2 (April 2021) - Patsalides, Athos; Santillan, Alejandro; Sundararajan, Sri Hari; Michael, Marissa; Suurna, Maria; Alexiades, George
Objectives: This prospective study evaluates the effectiveness and safety of venous sinus stenting for patients with isolated pulsatile tinnitus and lateral sinus stenosis. Methods: Patients with isolated pulsatile tinnitus and lateral sinus stenosis with a minimum trans stenotic gradient of 4 mm Hg were treated with stenting. Pulsatile tinnitus before and after treatment was assessed with the Tinnitus Handicap Inventory (THI). Periprocedural adverse events, neurological complications, clinical and radiographic follow-up were also recorded. Results: A total of 42 patients (41 females and 1 male) were included in the study (median age of 37.5 years). Thirty patients had post-stenotic fusiform and 12 had post-stenotic saccular venous sinus aneurysm. In addition to stenting, coils were used to treat the patients with saccular venous aneurysms. The median follow-up was 5 months (range 1 to 34 months). Most patients had complete (39/42) or near-complete (2/42) resolution of their pulsatile tinnitus post-procedure. There were no serious adverse events. Conclusion: Stenting of the lateral venous sinus is a safe and effective treatment for patients with isolated pulsatile tinnitus due to venous sinus stenosis.